The cultural unconscious and the contradictions of the implicit sectarian belief of left-wing poets in Iraq - مطر, ناجي عباس مطر (Journal of College of Education, 2023)
The innate affiliation of the human being keeps permeating the depths of the human being, where they will not be freed from its influences, even if, in later stages of life, they will adopt ideologies that intersect therewith, because that affiliation is deposited in the human conscience as a cultural ferment that leaves its mark on all the choices that a person makes in his (or her) life. The sect represents one of the most important elements of initial affiliation. It constitutes the first map of the human being awareness and interpretation, as he reshapes his position towards the world in his early awareness based on the interpretations provided by the sect’s heritage and its cultural memory of the phenomena, concepts and things surrounding him. If we follow the manifestations of those cultural sediments in the poetic production of Iraqi Marxist poets, we will find a clear effect of this in spite the obvious ideological intersection between sects and Marxism in general. In my opinion, the sect, its symbolism and figures represent an intimate and unavoidable emotional memory. Thus, it manifests itself clearly and dominantly in the works of the Iraqi left-wing poets, who are supposed to have been liberated from the mantle of religion and its theoretical influences. They are residuals that have cast a strong shadow to the extent that the semantic pairing between ideological symbolism and sectarian symbolism often seems to be hybrid, albeit in some respects tilted in favour of sympathizing with the sectarian symbol at the expense of the ideological as a kind of emotional lure for the recipient to the cultural commonality area that associate him with a known recipient and a specific imagined reader.